The HERMES-13 macroeconomic model of the Irish economy - Adele Bergin; Thomas Conefrey; John FitzGerald; Ide Kearney; Nuša Žnuderl (The Economic and Social Research Institute (ESRI), 2013)
The HERMES macroeconomic model has been used extensively for over 25 years to carry out medium-term forecasting and scenario analysis of the Irish economy. Most recently the model has been used to generate the scenarios underpinning the 2013 edition of the ESRI's Medium-Term Review. In the long period over which the model has been used for policy analysis, the Irish economy has undergone substantial change and new approaches to modelling important economic relationships have been developed. This paper outlines the structure and behaviour of the most recent version of the HERMES model (HERMES-13). We describe the key mechanisms and the modelling innovations which have been introduced to deal with major changes in the economy. As the model draws on a range of research on the Irish economy, we describe how this work has been incorporated into the model to better capture key economic relationships. Finally, we examine the results of a series of shocks to key variables carried out using the model. This provides a benchmark against which to evaluate the long-run properties of the model as well as illustrating how the model can shed light on the key transmission channels in the economy. This paper, and the accompanying detailed model listing and estimation output, provides a basic reference manual that practitioners and interested parties can use to interpret model output and, it is hoped, make suggestions for further model development and improvement.
Keywords: 330